The Influence of Customers Satisfaction and Consumer Loyalty on Corporate Reputation - maulida natswa, fida; Winanti, Winanti; Adella, Adella; Indri Nurwati, Mega; Sidiq, Ilham; Riyanto, Fajar (Journal of E-business and Management Science, 2024)
Corporate reputation reflects the perception of the public, stakeholders, and customers toward a company. This study aims to analyze the influence of customer satisfaction and consumer loyalty on corporate reputation at PT XYZ, both collectively and partially. Data was collected through a survey of 91 customers, determined using the non-probability quota sampling technique. Primary data was obtained through questionnaires and analyzed using SPSS Version 18.0, employing validity and reliability tests, classical assumption tests, determination coefficient tests, correlation tests, and hypothesis testing with F-test and T-test. The results showed a moderate correlation (0.435) between customer satisfaction, consumer loyalty, and corporate reputation, with a determination coefficient of 18.9%, indicating that 81.1% is influenced by other variables not included in this study. Hypothesis testing revealed F-calculated (10.249) > F-table (3.100), confirming a dominant influence of customer satisfaction and consumer loyalty on corporate reputation. Regression analysis produced the equation Y = 12.454 + 0.328X₁ + 0.444X₂, indicating a positive and significant effect. These findings emphasize the importance of customer satisfaction and consumer loyalty in enhancing corporate reputation at PT XYZ